Predication: The Test For Tax Avoidance in New Zealand From Newton to Ben Nevis - Prebble, John; McIntosh, Hamish (Victoria University of Wellington Law Review, 2015)
General anti-avoidance rules in income tax legislation are a blunt instrument. They can operate most effectively when decision makers move directly from the rule, such as "Arrangements with the purpose of tax avoidance are void against the Commissioner" to the facts, for example, "Objectively, do these facts demonstrate a purpose of avoidance?", or to paraphrase Lord Denning's test, "Viewing these facts objectively, can one predicate an avoidance purpose?" New Zealand courts adopted Lord Denning's "predication test" in 1966, but later cases confused things by trying to incorporate sub-rules into the exercise of looking for an avoidance purpose. Parliament codified and strengthened the predication test in 1974. Inland Revenue Department archives show that strengthening and codification of the test was what was intended and the language of the amendment confirms this intention. Nevertheless, later judgments misunderstood what the predication test entailed, and mistakenly thought that Parliament intended the 1974 amendment to abolish the test and to replace it with something else. In 2009 the Supreme Court delivered its judgment in Ben Nevis Forestry Ventures Ltd v Commissioner of Inland Revenue, the first case on tax avoidance to come before the Court. The Court said that the 1974 amendment abolished the predication test, but its reasoning in deciding the Ben Nevis case was in effect an exercise in predication. It would be useful to employ a name for the Supreme Court's approach to tax avoidance because a name would enable people to refer to the Supreme Court's test without circumlocution. "Predication" is the appropriate name because of its accuracy as to the meaning required and because of its historical antecedents.